Modelagem numérica do comportamento estrutural de vigas mistas de aço e concreto protendidas - Silva, Elder Nogueira da (2018)
The structural behavior of the prestressed steel concrete composite beams was investigated using the Finite Element Method. The present study reports two types of composite beams: steel beams and concrete slab with joint work ensured for shear connectors, in a traditional way and partially encased composite beams. Initially, were presented and discussed the characteristics, advantages, disadvantages, applications and constructive aspects of this structural system, that can be used in the recovery and rehabilitation of existing structures or in new large structures design. Subsequently, were presented analytical expressions for the size of this structures. A numerical analysis methodology, that is, a modeling strategy using software ABAQUS® was developed and calibrated based on available bibliography experimental results for both types of composite beams presents in this paper. The composite beams of the conventional typology were modeled in two ways: interaction steel-concrete established with the perfect coupling of all the common nodes through TIE constraint; and interaction steel-concrete established with modeling of shear connectors and using contact interaction between surfaces. The partially encased composite beam was initially modeled and calibrated without application of the prestressing force, for later modeling of the tendons, due the misses of experimental results of the prestressed partially encased composite beams. The numerical methodology presents aspects related to the choice of finite elements used, mesh geometry, constitutive relations of materials, interaction between materials and loading procedures. Finally, a parametric study was developed for the composite beams with conventional typology. The objective of this study was analyzing the influence of the variation of the tendon eccentricity; of the variation of the tendon force and the influence of the layout of the prestressing tendons. In general, the modeling strategy for conventional composite beam was adequate to simulate its structural behavior, especially for the case where the interaction steel-concrete was established by the shear connectors. In the case of partially encased composite beams, was possible to see the effects of the prestressing on its structural behavior, due to the increase in the ultimate moments carrying capacity; smaller displacements and smaller deformations. In additions, there were good correlations of the ultimate moment carrying capacity obtained analytically and numerically.